Designing Web Based Offering and Sales Information System (Case Study : PT. Daya Berkah Sentosa Nusantara) - Siti Nurjanah Ramadhany; Ade Eviyanti (Universitas Muhammadiyah Sidoarjo, 2021)
Technology is increasingly sophisticated with over time competition in the business world such as E-Commerce has a positive impact on entrepreneurs to advance their companies, namely by creating online websites so that offerings and sales are easy among the public. By accessing the website page of PT. Daya Berkah Sentosa Nusantara buyers do not have to come directly to the place or company, and send offers according to admin needs.The purpose of this study is to make it easier for researchers to solve supply and sales problems based on problems that arise in the company. The method used in this study is the Waterfall Method, with data collection techniques used using observation, interviews and literature study. The desired result of this research is to be able to create a website for the company, to be able to expand marketing reach, buyers can view products through the website.